In situ irregularity identification and scintillation estimation using wavelets and CINDI on C/NOFS. Issue 4 (2nd August 2013) - Stoneback, R. A.; Heelis, R. A.; Caton, R. G.; Su, Y.‐J.; Groves, K. M.
<x xml:space="preserve">Abstract</x> [1] Wavelets are a time‐domain method that is able to extract both time and frequency information from a signal. The Morlet wavelet is used here to characterize the magnitude of ionospheric irregularities using measurements of the total ion density from the Coupled Ion Neutral Dynamics Investigation package onboard the Communications/Navigation Outage Forecasting System spacecraft. The power in ionospheric irregularities at scale sizes less than 128 km is used to generate an irregularity amplitude index. This index is used with a phase screen analysis to form an estimate of scintillation at the satellite location. The temporal information retained in a wavelet analysis also allows for an accurate power spectrum calculation even when used on short segments of data which is useful for real‐time processing of irregularity detection onboard a satellite or for analyzing the long data sets produced by a satellite. To validate the process, a comparison of the in situ scintillation estimate and Scintillation Network and Decision Aid measurements of the S4 index is presented.